Kronik obstrüktif akciğer hastalarında fonksiyonel performans ve etkileyen faktörler - Gülseven, Bilgi (My University, 2005)
FUNCTIONAL PERFORMANCE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND INFLUENTIAL FACTORS SUMMARY The research has been planned and conducted methodologically, descriptively, and analytically in order to evaluate the validity and reliability of the Turkish versions of the tools, Functional Performance Inventory (FPI), FPI Importance of Functioning Scale (IFS), and FPI Satisfaction with Functioning Scale (SFS); and to define the functional performance levels and influential factors, and the correlations between functional performance, importance and satisfaction levels in patients with COPD. The scope of the research covered patients with COPD who have applied to the Chest Diseases Department of Marmara University Medical Faculty between dates May, 2003 - February, 2004 and the Chest Diseases Department of İstanbul University Medical Faculty between dates September, 2003 - February, 2004. The sample consisted 110 patients with COPD who accepted to participate the study and who have met the inclusion criteria, defined with respect to the literature knowledge. Patient Information Form, and the scales FPI, IFS, and SFS, developed by N. K. Leidy were used during data collection. During the data analysis; percentage rates, arithmetical averages, standard deviation, minimum and maximum values, X2, Student's t, Mann-Whitney U, Kruskall Wallis tests, Pearson and Spearman Correlation Analysis, Item Total Score Correlation and Cronbach's Alpha techniques were used. At the end of the research, it was defined that; ·FPI (?=0.93), IFS (?= 0.77) and SFS (?= 0.90) were valid and reliable tools to be used in our country, ·the score averages the patients received from FPI was 1.74±0.41, from IFS 2.42±0.44, from SFS 1.57±0.68, with no statistically significant differences between the obtained scores in relation to sexes (p>0.05), ·there were statistically high significant positive correlations between patients' scores from FPI and SFS (r=0.25-0.73, p<0.01), ·there were statistically high significant positive correlations between the scores patients received from FPI and the percent of predicted FEV1 (p<0.01). Key Words: Nursing, Functional Performance, Chronic Obstructive Pulmonary Disease (COPD) KRONİK OBSTRÜKTİF AKCİĞER HASTALARINDA FONKSİYONEL PERFORMANS VE ETKİLEYEN FAKTÖRLER Adı ve Soyadı:Bilgi Gülseven Danışmanın Adı:Prof.Dr. Necmiye Sabuncu Doktora Hemşirelik Esasları ABD

Araştırma; KOAH'lı hastalarda, Fonksiyonel Performans Envanteri-FPE, Fonksiyon Önem Ölçeği-FÖÖ ve Fonksiyon Doyum Ölçeği-FDÖ'nin Türkçe şeklinin geçerlik ve güvenirliğini değerlendirmek; fonksiyonel performans düzeyi ve etkileyen faktörleri, fonksiyonel performans, önem ve doyum düzeyi arasındaki ilişkiyi belirlemek amacıyla metodolojik, tanımlayıcı ve analitik olarak planlandı ve gerçekleştirildi Araştırmanın evrenini, Mayıs 2003- Şubat 2004 tarihleri arasında M.Ü. Tıp Fakültesi Hastanesi Göğüs Hastalıkları Eylül 2003- Şubat 2004 tarihleri arasında İ.Ü. Tıp Fakültesi Hastanesi Göğüs Hastalıkları vuran KOAH'lı hastalar; örneklem grubunu ise bu hastalar arasından literatür bilgisine dayalı olarak belirlenen kriterlere uyan ve araştırmaya katılmayı kabul eden KOAH'lı 110 hasta oluşturdu. Veri toplanmasında Hasta Bilgi Formu ve N.K. Leidy tarafından geliştirilen FPE, FÖÖ ve FDÖ kullanıldı. Veri analizinde; yüzdelik oran, aritmetik ortalama, standart sapma, minimum ve maksimum değerler, X², Student's t, Mann-Whitney U, Kruskall Wallis testleri, Pearson ve Spearman Korelasyon analizi, Madde Toplam Puan Korelasyonu ve Cronbach's Alpha tekniği kullanıldı. Araştırmanın sonucunda; ·FPE (?=0.93), FÖÖ (?= 0.77) ve FDÖ (?= 0.90)'nin ülkemiz için geçerli ve güvenilir olduğu, ·Hastaların FPE'den aldıkları puan ortalamasının 1.74±0.41, FÖÖ'den aldıkları puan ortalamasının 2.42±0.44, FDÖ'den aldıkları puan ortalamasının 1.57±0.68 olduğu ve cinsiyete göre alınan puanlar açısından istatistiksel olarak anlamlı fark olmadığı (p>0.05), ·Hastaların FPE ve FDÖ'den aldıkları puanlar arasında istatistiksel olarak ileri derecede anlamlı pozitif korelasyonlar olduğu (r=0.25-0.73 ve p<0.01), ·Hastaların FPE'den aldıkları puanlar ve beklenen FEV1 %'si arasında istatistiksel olarak ileri derecede anlamlı pozitif korelasyonlar olduğu (p<0.01) belirlendi. Hemşirelik, Fonksiyonel Performans, Kronik Obstrüktif Akciğer Hastalığı (KOAH)
Keywords: Akciğerler_Hastalıklar; araştırma; Eğitim; hemşirelik; Hemşirelik ve tıp teknisyenleri ve yardımcı personel; Teknoloji (Uygulamalı bilimler); Tıp bilimleri